239/240Pu Dispersion Modeling for Emergencies During Nuclear Power Plant Operations in Malaysia - Muslim Muslim; Sa'iyd Husayn Ahmadi; Jarot Marwoto; Heny Suseno; Yvette Agyiriba Aggrey (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2022)
The East Coast of Johor in Malaysia is a strategic area as a candidate site for nuclear power plants. Its location is near coastal area and is therefore convenient to use seawater as a source of cooling for power plants. This makes the East Malaysia waters, and their surroundings stand a high risk of direct radioactive contamination, especially in event of an accident. Pu is a non-conservative or reactive radionuclide that easily settles with particles and has high radiotoxicity and radiochemistry, making it very dangerous. The purpose of this study was to determine the distribution patterns of 239/240Pu releases in the waters of East Malaysia and the surrounding waters. To determine the affected areas due to 239/240Pu pollution using MIKE flow flexible mesh module and particle tracking module. The magnitude of 239/240Pu used in this model is based on the disaster in Fukushima Daiichi in 2011. This research can be used as a mitigation of 239/240Pu pollution when a nuclear reactor disaster occurs in the area around Indonesia's territorial border. Discharge of 239/240Pu was simulated during the west and east monsoons season which result in the distribution pattern following the seasonal flow pattern. During the west monsoon, the dispersion speed of 239/240Pu is four times faster than the east monsoon. The 239/240Pu distribution is predominantly towards the south, however, the contaminated area was only occurred on the coast of Johor and does not extend to the waters of Indonesia.